Beyond Connectivity: Quantifying the Economy-Wide Impact of Non-Toll Road Preservation via Public-Private Partnerships - Emmir, Arga (Department of Public Administration, Parahyangan Catholic University, 2026)
The escalating imperative for resilient infrastructure in developing economies often competes with fiscal constraints, necessitating innovative financing models such as Public-Private Partnerships (PPP). While extensive literature examines the economic impact of new toll road construction, empirical evidence regarding the economy-wide valuation of non-toll road preservation remains scarce. This study investigates the national economic repercussions of the South Sumatra Eastern Highway preservation project, Indonesia’s inaugural non-toll PPP initiative, employing a rigorous Input-Output analysis updated to 2023. By integrating Keynesian multipliers with Hirschman’s unbalanced growth theory, the research quantifies the project’s capacity to catalyze sectoral linkages. The findings reveal that the preservation investment generates a total output multiplier of 1.76, creating substantial employment opportunities, primarily within the construction sector. Furthermore, the analysis uncovers significant compulsive backward linkages, where the preservation activities actively stimulate upstream industries, particularly manufacturing and wholesale trade, despite these sectors not receiving direct investment. These results challenge the perception that maintenance projects yield lower economic returns than new construction. This study provides a robust justification for expanding PPP schemes in asset preservation, demonstrating that strategic maintenance is not merely a cost but a potent driver of intersectoral economic growth and structural development.